First and Second Line Highly Active Anti-Retroviral Therapy Failure in HIV Infected Nigerian Children at University of Abuja Teaching Hospital Gwagwalada, Nigeria - Adaora A Okechukwu; Frank I Amajuoyi (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Background: In high-income countries, viral load is routinely used for monitoring HIV patients on antiretroviral therapy for early detection of drug failure. This is not the case in most resource limited settings like ours where only WHO immunological and clinical criteria are used for monitoring. This study is aimed at determining the rate/time of failure to 1st and 2nd antiretroviral drugs in children in our centers. Method: Is a retrospective study of children ≤18 years switched to 2nd line antiretroviral regimen and those requiring third line drugs from Jan 2006 to June 2015 in our health institution. Data analysis was conducted using SPSS version 16.0 software and statistical significance set at p < 0.05. Result: Sixteen percent (82/514) of children on 1st line medication were switched to 2nd line drugs with switch over rate of 9 persons/year, and 6/82 (7.3%) required 3rd line medication. The median switch over time was 31.3 months (IQR 26.4-36.2) for 2nd line medication, and 42.6 months (IQR 40.1-44.3) from time of switch to 2nd line drugs for those requiring 3rd line regimen. Over 90% of patients switched to 2nd line drugs were between 9-18 years, none was an infant. The mean CD4 cell count and viral load before switch to 2nd line drugs was 109.09±29.23 cell/mm3 and 180,480.29±35,303 copies/ml, and 89.42±28.67 cell/mm3/ 237,337.5±64,619 copies/ml for those requiring 3rd line medications.There was over 450 fold increase in viral load from the expected undetectable level of 400 copies/ml after 6 months on medication before patients were switch to 2nd line drugs, and over 590 folds increase for those that require 3rd line medications. Significant difference was seen in the mean CD4 cell count and weight of those with adherence of ≥ 95% and ≤ 95% (p values were <0.05). Conclusion: WHO immunological and clinical criteria were found not to be ideal for monitoring of children on antiretroviral therapy. Six monthly viral load monitoring and resistance testing should be introduced in Nigerian guideline for managing HIV children for better therapeutic and pharmacoeconomic outcomes. Third line medication should also be made available in the country and intensification of adherence is required in adolescent age group.